Household consumers’ behaviour: factors influencing food waste generation in Malaysia - Abdul Aziz, Nur Saidatul Filzah; Zaharuddin, Nurul Aisyah; Mohd Isa, Sulaiha; A. Bakar, Siti Khuzaimah; Abdul Karim, Noraida (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Food waste has become a pressing global concern with social, economic, and environmental implications. In Malaysia, households are among the largest contributors to food waste; yet, the behavioural factors driving this issue remain underexplored. Guided by the Theory of Planned Behaviour, this study examines the influence of diet preferences, purchasing discipline, and family stage and lifestyle on household food waste generation. Data were collected through a structured survey of Malaysian households (n = 348) and analysed using SmartPLS 4. The measurement model indicated acceptable reliability (Composite Reliability = 0.752–0.809) but low convergent validity (Average Variance Extracted = 0.299–0.310), reflecting the complexity of measuring culturally embedded food practices in Malaysia. All items were retained to preserve content validity. Structural model analysis revealed that two (2) predictors were positively associated with food waste. Diet Preferences (β = 0.174, f² = 0.026) had small effects, while Family Stage and Lifestyle (β = 0.420, f² = 0.192) emerged as the strongest predictor with a medium effect size. The predictors explained 36.3% of the variance in household food waste generation (R² = 0.363), reflecting moderate explanatory power. These findings highlight that family composition and lifestyle patterns are central to household food waste in Malaysia. Policy interventions should therefore prioritise family- and lifestyle-focused education, complemented by initiatives promoting better purchasing habits and meal planning. Such strategies can help reduce waste while aligning with local cultural norms and daily practices.